Validated RP-HPLC and HPTLC methods for simultaneous estimation of febuxostat and diclofenac sodium in pharmaceutical dosage form - Sunitha, Ponnuveetil Gopi; Ilango, Kaliappan (European Journal of Chemistry, 2014)
The present work reports a reverse phase high performance liquid chromatography (RP-HPLC) method and high performance thin layer chromatography (HPTLC) method for the simultaneous determination of febuxostat and diclofenac sodium in pharmaceutical dosage form. HPLC was performed using a Thermo Hypersil C18 column (250 × 4.6 mm i.d., 5 μm particle size) using a mixture of methanol: KH2PO4 (0.02 M) (70:30, v:v) as mobile phase. Ultraviolet detection was carried out at 280 nm. The retention time of febuxostat and diclofenac sodium were found to be 6.725 and 8.892 min, respectively. The HPTLC separation was conducted on Merck HPTLC aluminum sheets of silica gel 60 F254 as stationary phase using toluene:methanol in the ratio of 7:3 (v:v) as the mobile phase. The detection of febuxostat and diclofenac sodium was carried out at 297 nm. The Rf values of febuxostat and diclofenac sodium were found to be 0.48 and 0.60, respectively. Both the methods were validated as per ICH guidelines. The proposed methods were found to be suitable for the quantification of the selected combination of drugs in pharmaceutical dosage form.